Pancasila Berkehidupan Dalam Etika Kebangsaan - Emmi Kholilah Harahap (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
Every nation who wants to stand firm and know clearly where the goal is to achieve it requires a view of life. With this view of life a nation will look at the problems it faces and determine the direction and the way how to solve these problems. Without a view of life then a nation will feel vacillated in facing big problems that will surely arise, both the problems within the community itself, as well as the big problems of human beings in the association of the peoples of the nations of the world. With a clear view of life a nation will have guidance and guidance on how it solves the political, economic, social and cultural problems arising in the advancing societies. By referring to the view of life that also a nation will build itself. As the philosophy of the state, of course Pancasila there who formulate it. Pancasila is indeed the greatest gift of Allah SWT and it turns light for all the Indonesian people in the future, both as a guideline in fighting for independence, as well as a unifying tool in the life of national harmony, as well as a view of life for everyday Indonesian human life, and which has clearly been expressed as the basis and philosophy of the Republic of Indonesia. Pancasila has existed in all forms of Indonesian people's life, except for those who are not Pancasila. Pancasila was born June 1, 1945, set on August 18, 1945 together with the 1945 Constitution. The correct sounds and speech of Pancasila based on Presidential Instruction No. 12 of 1968 is one, Belief in the One Supreme. Two, a just and civilized humanity. Three Unity Indonesia. Four, Democracy led by the wisdom of wisdom in deliberations / representation. And fifth, social justice for all the people of Indonesia.